Health and Health Seeking in Mosul During ISIS Control and Liberation: Results From a 40-Cluster Household Survey. (28th March 2019) - Lafta, Riyadh; Cetorelli, Valeria; Burnham, Gilbert
ABSTRACT: Objectives: ISIS seized Mosul in June 2014. This survey was conducted to assess health status, health needs, and health-seeking behavior during ISIS control and the subsequent Iraqi military campaign. Methods: Forty clusters were chosen: 25 from east Mosul and 15 from west Mosul. In each, 30 households were interviewed, representing 7559 persons. The start house for each cluster was selected using satellite maps. The survey in east Mosul was conducted from March 13–31, 2017, and in west Mosul from July 18–31, 2017. Results: In the preceding 2 weeks, 265 (5.4%) adults reported being ill. Some 67 (25.3%) complaints were for emotional or behavioral issues, and 59 (22.3%) for noncommunicable diseases. There were 349 (13.2%) children under age 15 reportedly ill during this time. Diarrhea, respiratory complaints, and emotional and behavioral problems were most common. Care seeking among both children and adults was low, especially in west Mosul. During ISIS occupation, 640 (39.0%) women of childbearing age reported deliveries. Of these, 431 (67.3%) had received some antenatal care, and 582 (90.9%) delivered in a hospital. Complications were reported by 417 (65.2%). Conclusions: Communicable and noncommunicable diseases were reported for both children and adults, with a high prevalence of emotional and behavioral problems, particularly in west Mosul. Care-seeking was low, treatment compliance for noncommunicable diseases was poor, and treatment options for patients were limited. ( Disaster Med Public Health Preparedness . 2019;13:758–766)